Seismic Behavior Improvement of Rigid Steel Frame Braced with Cable and Optimal Rotational Friction Damper - Pouya Azarsa; Saleh Abdul Amir Mohammad; Abdullah I. Almansour; Dejian Shen (Buildings)
The research focused on enhancing the seismic performance of steel moment frames using cable braces and a central friction damper. By optimizing the design and pretensioning force of the cable braces, this study aimed to improve the energy absorption and overall behavior of the frames under cyclic earthquake loads. A quasi-cyclic loading test was developed through FE simulations using ABAQUS software, version 2023. To verify the modeling, an experimental test was compared with the numerical modeling, and the numerical results confirmed the accuracy of the experimental data. Results made by modeling in ABAQUS software (version 2023) include the impact of pretensioning force on stiffness and energy absorption, the relationship between pretensioning force and force required to move the target, the increase in absorbed energy with pretension force up to 25%, and the superior seismic performance of frames with rotational friction dampers. This study also highlighted the benefits of using cable braces with a friction damper regarding the symmetry of hysteresis diagrams, cyclic performance, and energy absorption capacity. The amount of pretensioning of the cables affects the energy dissipation capacity. As the pretensioning of the cables increases, the energy dissipation capacity initially increases. However, further increases in pretensioning lead to decreased energy dissipation capacity beyond a certain point. When the percentage of cable brace pretension increases from 2% to 25%, the energy dissipation capacity is enhanced by 2%, and when in the 25–30% range, it stabilizes at around 35%. Energy dissipation capacity decreases for pretensions of more than 30%.